A Comparative Analysis on the role of Husbands of Housewives (HHWs) and Professional Ladies (HPLs) in the Education of their Children: A case Study of the rural areas of Sindh, Pakistan - Zafar Iqbal; Mamdouh, Ayman Aied Mohammed (Technium Social Sciences Journal, 2021)
A research was conducted on the husbands of the Housewives and Professional Ladies in the rural areas of Tando Allahyar, Sindh. A questionnaire was designed consisted of 10 questions to the Husbands of House Wives and Professional Ladies having less than 360 US per Annum and less than K-10 education. To analyze the data, SPSS software was used. All percentages, Means and SD were find through SPSS software. The data was tabulated, presented and analyzed at the end of every table. 25 husbands in each group were chosen as population. After results analyzing it was found as that Husbands of HWs believe that their wives were good sort of teachers for their children. HHWs felt difficulty than HPLs while teaching or helping their children. HHWs were more comfortable with the jobs of their wives. HWs were playing better jobs in homes. HPLs teach effectively the children than the HHWs. HPLs were better husbands than the HHWs. HPLs were more satisfied with the moral aspects of their children. HPLs were playing better jobs in that field. HPLs were more satisfied with the role of their wives in developing the personality. HPLs were giving more information and knowledge than their mothers. HPLs were playing better jobs in that field. Husbands were major source of information for children. HPLs and HHWs both teach about religious duties to their children. Fathers are major source of information for children.